PENGEMBANGAN MODEL EKO-AGROWISATA DI DESA CISAAT KECAMATAN CIATER KABUPATEN SUBANG PROVINSI JAWA BARAT - Revi Agustin Aisyianita (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2020)
Cisaat village is located in Ciater district, Subang which known as agriculture and farm area. Most of society in Cisaat village work as farmer. Agriculture and farm area have become favourite tourist spot recently due to the back to local trend. Today's tourists trend to seek unique travel experiences by visiting natural place. However, the experience of traveling will not be optimal if it is not accompanied by various tourist activities and interactions with the surrounding community. Eco agrotourism is an alternative model of tourism that can be applied in Cisaat village. Natural beauty, fresh air, friendly people make this village suitable to be developed as an eco agrotourism attraction.This research was conducted with the purpose of (1) identifying potential attractions, amenities, and accessibility in Cisaat Village (2) and formulating an eco agrotourism development model in Cisaat Village. The collected data method uses literature study techniques and direct observation to the field. Through this research, it is hoped that Cisaat Village will be able to develop its potential into a new tourism product that can increase economic added value and sustainable.